Glycodendrimers: tools to explore multivalent galectin-1 interactions - Cousin, Jonathan M.; Cloninger, Mary J. (Beilstein Journal of Organic Chemistry, 2015)
Four generations of lactose-functionalized polyamidoamine (PAMAM) were employed to further the understanding of multivalent galectin-1 mediated interactions. Dynamic light scattering and fluorescence microscopy were used to study the multivalent interaction of galectin-1 with the glycodendrimers in solution, and glycodendrimers were observed to organize galectin-1 into nanoparticles. In the presence of a large excess of galectin-1, glycodendrimers nucleated galectin-1 into nanoparticles that were remarkably homologous in size (400–500 nm). To understand augmentation of oncologic cellular aggregation by galectin-1, glycodendrimers were used in cell-based assays with human prostate carcinoma cells (DU145). The results revealed that glycodendrimers provided competitive binding sites for galectin-1, which diverted galectin-1 from its typical function in cellular aggregation of DU145 cells.
Keywords: dendrimer; galectin-1; glycodendrimer; multivalent; nanoparticle

(untitled) - Astorgues-Xerri, L.; Riveiro, M. E.; Tijeras-Raballand, A.; Serova, M.; Neuzillet, C.; Albert, S.; Raymond, E.; Faivre, S. (Cancer Treat. Rev., 2014)

(untitled) - Camby, I.; Le Mercier, M.; Lefranc, F.; Kiss, R. (Glycobiology, 2006)

(untitled) - Liu, F.-T.; Rabinovich, G. A. (Nat. Rev. Cancer, 2005)

(untitled) - Rabinovich, G. A. (Br. J. Cancer, 2005)

(untitled) - Barondes, S. H.; Castronovo, V.; Cooper, D. N. W.; Cummings, R. D.; Drickamer, K.; Feizi, T.; Gitt, M. A.; Hirabayashi, J.; Hughes, C.; Kasai, K.; Leffler, H.; Liu, F.-T.; et al. (Cell, 1994)

(untitled) - Barondes, S. H.; Cooper, D. N. W.; Gitt, M. A.; Leffler, H. (J. Biol. Chem., 1994)

Galectins - Klyosov, A. A.; Witczak, Z. J.; Platt, D. (Wiley, 2008)

(untitled) - Brewer, C. F. (Glycoconjugate J., 2002)

(untitled) - Suzuki, O.; Abe, M. (Int. J. Oncol., 2014)

(untitled) - D'Haene, N.; Sauvage, S.; Maris, C.; Adanja, I.; Le Mercier, M.; Decaestecker, C.; Baum, L.; Salmon, I. (PLoS One, 2013)

(untitled) - Brewer, C. F. (Biochim. Biophys. Acta, Gen. Subj., 2002)

(untitled) - Belardi, B.; O'Donoghue, G. P.; Smith, A. W.; Groves, J. T.; Bertozzi, C. R. (J. Am. Chem. Soc., 2012)

(untitled) - Hernandez, J. D.; Nguyen, J. T.; He, J.; Wang, W.; Ardman, B.; Green, J. M.; Fukuda, M.; Baum, L. G. (J. Immunol., 2006)

(untitled) - Wang, J.; Lu, Z.-H.; Gabius, H.-J.; Rohowsky-Kochan, C.; Ledeen, R. W.; Wu, G. (J. Immunol., 2009)

Galectins: Methods and Protocols - Mancini, S. J. C.; Elantak, L.; Boned, A.; Espeli, M.; Guerlesquin, F.; Schiff, C. (Examination of Galectin-Induced Lattice Formation on Early B-Cell Development, 2015)

(untitled) - Bojić-Trbojević, Z.; Krivokuća, M. J.; Kolundžić, N.; Petronijević, M.; Vrzic-Petronijević, S.; Golubović, S.; Vićovac, L. (Histochem. Cell Biol., 2014)

(untitled) - Huang, Y.-J.; Shiau, A.-L.; Chen, S.-Y.; Chen, Y.-L.; Wang, C.-R.; Tsai, C.-Y.; Chang, M.-Y.; Li, Y.-T.; Leu, C.-H.; Wu, C.-L. (Eur. Cells Mater., 2012)

(untitled) - Sacchettini, J. C.; Baum, L. G.; Brewer, C. F. (Biochemistry, 2001)

(untitled) - Brewer, C. F.; Miceli, M. C.; Baum, L. G. (Curr. Opin. Struct. Biol., 2002)

(untitled) - Garner, O. B.; Baum, L. G. (Biochem. Soc. Trans., 2008)

(untitled) - López-Lucendo, M. F.; Solis, D.; André, S.; Hirabayashi, J.; Kasai, K.; Kaltner, H.; Gabius, H.-J.; Romero, A. (J. Mol. Biol., 2004)

(untitled) - Mammen, M.; Choi, S.-K.; Whitesides, G. M. (Angew. Chem., Int. Ed., 1998)

(untitled) - Gestwicki, J. E.; Strong, L. E.; Cairo, C. W.; Boehm, F. J.; Kiessling, L. L. (Chem. Biol., 2002)

(untitled) - Kiessling, L. L.; Gestwicki, J. E.; Strong, L. E. (Curr. Opin. Chem. Biol., 2000)

(untitled) - Kiessling, L. L.; Gestwicki, J. E.; Strong, L. E. (Angew. Chem., Int. Ed., 2006)

(untitled) - Lee, Y. C.; Lee, R. T. (Acc. Chem. Res., 1995)

(untitled) - Tejler, J.; Tullberg, E.; Frejd, T.; Leffler, H.; Nilsson, U. J. (Carbohydr. Res., 2006)

(untitled) - André, S.; Ortega, P. J. C.; Perez, M. A.; Roy, R.; Gabius, H.-J. (Glycobiology, 1999)

(untitled) - Tinari, N.; Kuwabara, I.; Huflejt, M. E.; Shen, P. F.; Iacobelli, S.; Liu, F.-T. (Int. J. Cancer, 2001)

(untitled) - Iurisci, I.; Cumashi, A.; Sherman, A. A.; Tsvetkov, Y. E.; Tinari, N.; Piccolo, E.; D'Egidio, M.; Adamo, V.; Natoli, C.; Rabinovich, G. A.; Iacobelli, S.; Nifantiev, N. E.; et al. (Anticancer Res., 2009)

(untitled) - Belitsky, J. M.; Nelson, A.; Hernandez, J. D.; Baum, L. G.; Stoddart, J. F. (Chem. Biol., 2007)

(untitled) - Goodman, C. K.; Wolfenden, M. L.; Nangia-Makker, P.; Michel, A. K.; Raz, A.; Cloninger, M. J. (Beilstein J. Org. Chem., 2014)

(untitled) - Miller, M. C.; Klyosov, A. A.; Mayo, K. H. (Glycobiology, 2012)

(untitled) - Joshi, M. D.; Ahmad, R.; Yin, L.; Raina, D.; Rajabi, H.; Bubley, G.; Kharbanda, S.; Kufe, D. (Mol. Cancer Ther., 2009)

(untitled) - Jeschke, U.; Karsten, U.; Wiest, I.; Schulze, S.; Kuhn, C.; Friese, K.; Walzel, H. (Histochem. Cell Biol., 2006)

(untitled) - Yang, J.; Hlavacek, W. S. (Math. Biosci., 2011)

(untitled) - Esfand, R.; Tomalia, D. A. (Drug Discovery Today, 2001)

(untitled) - Clausse, N.; van den Brule, F.; Waltregny, D.; Garnier, F.; Castronovo, V. (Angiogenesis, 1999)

(untitled) - van den Brule, F. A.; Waltregny, D.; Castronovo, V. (J. Pathol., 2001)

(untitled) - Hughes, R. C. (Biochimie, 2001)

(untitled) - Ito, K.; Stannard, K.; Gabutero, E.; Clark, A. M.; Neo, S.-Y.; Onturk, S.; Blanchard, H.; Ralph, S. J. (Cancer Metastasis Rev., 2012)

(untitled) - Ahmad, N.; Gabius, H.-J.; Sabesan, S.; Oscarson, S.; Brewer, C. F. (Glycobiology, 2004)

(untitled) - Woller, E. K.; Walter, E. D.; Morgan, J. R.; Singel, D. J.; Cloninger, M. J. (J. Am. Chem. Soc., 2003)

(untitled) - Michel, A. K.; Nangia-Makker, P.; Raz, A.; Cloninger, M. J. (ChemBioChem, 2014)